Alignment control and atomically-scaled heteroepitaxial interface study of GaN nanowires; Nanoscale; Vol. 9, iss. 16 - Qingyun Liu; Baodan Liu; Wenjin Yang; Bing Yang; Xinglai Zhang; Labbe C. Christophe; Portier X. Xavier; An V. V. Vladimir Vilorievich; Xin Jiang (2017, 2017)
Title screen